Ag-based electrical contact material

CN122918378APending Publication Date: 2026-10-16YUNNAN PRECIOUS METALS LAB CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611393884.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

现有技术中稀土金属虽然对银基材料在晶粒细化和强化方面提升较为明显,但对于材料在使用过程中的抗电弧烧蚀这一最重要的电接触性能提升并不明显

Benefits of technology

[0013] The technical solution provided by this invention has the following beneficial effects: This invention utilizes Gd for solid solution strengthening of the silver matrix, while Nd and Y are mainly distributed on the grain boundaries within the silver matrix, primarily playing a grain boundary strengthening role. Furthermore, the interaction between Gd, Nd, Y, and Ag allows precipitates such as Ag5Nd, Ag5Y, and Ag5(YNd) to improve the electrical contact performance of Ag-based materials. Simultaneously, this invention employs induction melting, rolling, drawing, and vacuum heat treatment processes to react Gd, Nd, Y, and Ag, and controls the type, quantity, and size of the precipitates to obtain Ag-based electrical contact materials with excellent electrical contact performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918378A_ABST
    Figure CN122918378A_ABST
Patent Text Reader

Abstract

The application discloses an Ag-based electric contact material and belongs to the technical field of metal-based contact materials. The Ag-based electric contact material comprises the following elements in percentage by weight: Gd: 1% to 4.0%, Y: 0.01% to 1.0%, Nd: 0.01% to 1.0%, and the balance is Ag. The Ag-based electric contact material is prepared through the following steps in sequence: batching, induction smelting, room temperature rolling, first vacuum heat treatment, cold drawing, second vacuum heat treatment and third vacuum heat treatment. The Gd, Nd, Y and Ag are mutually reacted through the processes of induction smelting, rolling, drawing and vacuum heat treatment, and the types, quantity and size of precipitates are controlled, so that the Ag-based electric contact material with good electric contact performance and mechanical performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal-based contact materials technology, specifically relating to an Ag-based electrical contact material. Background Technology

[0002] Silver possesses excellent thermal conductivity, electrical conductivity, and corrosion resistance, making silver alloys and composite materials the most widely used electrical contact materials. However, silver exhibits poor mechanical properties and insufficient surface resistance to electric arcs, resulting in a short electrical life, unreliability during operation, and a tendency to fused and weld. Therefore, alloying or the preparation of second-phase composite materials are commonly used to improve the electrical contact performance of silver.

[0003] Rare earth elements, due to their unique electronic structure and resulting physicochemical properties, are known as "industrial vitamins" in materials research. The addition of rare earth elements to silver to prepare silver-based contact materials originated in the mid-1950s. Adding small amounts of rare earth elements not only improves the mechanical properties of silver alloys but also significantly enhances important electrical contact properties such as arc erosion resistance, weldability, and oxidation resistance. Research has been conducted both domestically and internationally on electrical contact materials composed of rare earth elements and Ag, resulting in the development of AgCe and Ag-Cu-Ce alloy electrical contact materials. While existing technologies show significant improvements in grain refinement and strengthening of silver-based materials, they do not significantly enhance the crucial electrical contact performance of arc erosion resistance during use. Summary of the Invention

[0004] To address or partially address the problems existing in related technologies, this invention proposes an Ag-based electrical contact material. This invention incorporates Nd, Gd, and Y elements into the Ag-based material, and improves the electrical contact performance of Ag by enhancing the interaction between Nd, Gd, Y, and Ag through the preparation method of the Ag-based electrical contact material.

[0005] This invention provides an Ag-based electrical contact material comprising the following elements in weight percentage: Gd: 1%–4.0%, Nd: 0.01%–1.0%, Y: 0.01%–1.0%, with the balance being Ag; The preparation method of the Ag-based electrical contact material includes the following steps: (1) Gd metal, Nd metal and Y metal are mixed according to the element ratio of the Ag-based electrical contact material; (2) The prepared materials are induction melted to obtain ingots; (3) Measure whether the element content on the top and bottom surfaces of the ingot is uniform. If it is not uniform, turn the bottom of the ingot upward and perform multiple smelting steps (2) until the element content on both the top and bottom surfaces of the ingot is uniform. (4) The material obtained in step (3) is rolled, subjected to a first vacuum annealing heat treatment, repeated drawing and a second vacuum annealing heat treatment to obtain wire; (5) The wire is subjected to a third vacuum annealing heat treatment to obtain Ag-based electrical contact material.

[0006] Preferably, the induction melting specifically includes: a vacuum degree <1×10 -2 Pa, and then argon gas with a pressure of 1.0 to 1.1 atmospheres and a purity of 99.999% is introduced for melting.

[0007] Preferably, the uniformity of elemental content on the top and bottom surfaces of the spindle is measured using an X-ray fluorescence analyzer.

[0008] Preferably, the rolling temperature is room temperature, and the deformation per rolling pass is 5-10%.

[0009] Preferably, the temperature of the first vacuum annealing heat treatment is 400-500℃, the time is 3 hours, and the vacuum degree is <1×10⁻⁶. -2 Pa.

[0010] Preferably, the drawing temperature is room temperature, and the deformation per pass is 3-4%.

[0011] Preferably, the second vacuum annealing heat treatment is performed at a temperature of 400-500℃ for 3 hours, with a vacuum degree <1×10⁻⁶. -2 Pa.

[0012] Preferably, the third vacuum annealing heat treatment is performed at a temperature of 800-850℃ for 0.5 hours, with a vacuum degree <1×10⁻⁶. -2 Pa.

[0013] The technical solution provided by this invention has the following beneficial effects: This invention utilizes Gd for solid solution strengthening of the silver matrix, while Nd and Y are mainly distributed on the grain boundaries within the silver matrix, primarily playing a grain boundary strengthening role. Furthermore, the interaction between Gd, Nd, Y, and Ag allows precipitates such as Ag5Nd, Ag5Y, and Ag5(YNd) to improve the electrical contact performance of Ag-based materials. Simultaneously, this invention employs induction melting, rolling, drawing, and vacuum heat treatment processes to react Gd, Nd, Y, and Ag, and controls the type, quantity, and size of the precipitates to obtain Ag-based electrical contact materials with excellent electrical contact performance. Attached Figure Description

[0014] Figure 1 The image shows the surface microstructure of the Ag-based electrical contact material prepared in Example 1 after an electrical contact test.

[0015] Figure 2This is a schematic diagram of an arc testing and imaging device. Detailed Implementation

[0016] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate this invention.

[0017] Example 1 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Nd: 0.01%, Y: 0.01%, with the balance being Ag.

[0018] The preparation method of the Ag-based electrical contact material includes the following steps: (1) Gd blocks, Nd blocks, Y blocks and Ag blocks are prepared according to the element ratio of Ag-based electrical contact material described above.

[0019] (2) Induction melting of the prepared materials: First, induction melting of the prepared materials is carried out in an alumina crucible, with a pre-vacuum degree of <1×10 -2 Pa, and then 99.999% argon gas at a pressure of 1.0 atmosphere is introduced for melting, and a cylindrical ingot is obtained through melting.

[0020] (3) After taking it out and polishing the top and bottom surfaces of the ingot, use an X-ray fluorescence analyzer to measure whether the contents of Y, Nd and Gd on the top and bottom surfaces of the ingot are uniform and whether the concentrations reach 0.01%, 0.01% and 1%, respectively. If they are not uniform and the concentrations do not reach the required levels, turn the bottom surface of the ingot upward and perform multiple smelting steps (2) until the contents of Y, Nd and Gd on both sides of the ingot are uniform.

[0021] (4) The material obtained in step (3) is rolled into a wire with a diameter of 10 mm at room temperature, with a deformation of 5-10% per rolling pass, under a vacuum degree <1×10 -2 Anneal at 400℃ for 3 hours in Pa.

[0022] (5) Then cold drawing, with a deformation of 3% per pass, and finally vacuum at 400℃ with a degree of <1×10 -2 Heat treatment at Pa for 3 hours, and repeated cold drawing and vacuum heat treatment were performed on the sample to obtain wire with a diameter of 1 mm.

[0023] (6) The filament is placed in a vacuum of <1×10 -2 Ag-based electrical contact materials were obtained by vacuum heat treatment at 800℃ for 0.5 hours in Pa.

[0024] Figure 1The image shows the microstructure of the Ag-based electrical contact material prepared in Example 1 after being subjected to an electric arc under harsh testing conditions of 25V / 30A DC. The image shows that the ablation pits from the arc are very small, large, and uniform, with virtually no visible material sputtering. This microstructure indicates that the material has strong resistance to arc ablation, making it a good electrical contact material. Typically, under these experimental conditions, common silver-based electrical contact materials (such as silver-tin oxide, silver-nickel, and silver-cerium) usually exhibit large pits due to concentrated arc ablation, as well as significant material sputtering, leading to rapid ablation and substantial material loss.

[0025] Example 2 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 4%, Nd: 1%, Y: 1%, with the balance being Ag.

[0026] The preparation method of the Ag-based electrical contact material includes the following steps: (1) Gd blocks, Nd blocks, Y blocks and Ag blocks are prepared according to the element ratio of Ag-based electrical contact material described above.

[0027] (2) Induction melting of the prepared materials: First, induction melting of the prepared materials is carried out in an alumina crucible, with a pre-vacuum degree of <1×10 -2 Pa, and then fill with 99.999% argon gas at a pressure of 1.1 atmospheres for melting, and obtain cylindrical ingots through melting.

[0028] (3) After taking it out and polishing the top and bottom surfaces of the ingot, use an X-ray fluorescence analyzer to measure whether the contents of Gd, Nd and Y on both sides of the ingot are uniform and whether the concentrations reach 4%, 1% and 1%, respectively. If they are not uniform and the concentrations do not reach the required levels, turn the bottom of the ingot up and perform multiple smelting steps (2) until the contents of Gd, Nd and Y on both sides of the ingot are uniform.

[0029] (4) The material obtained in step (3) is rolled into a wire with a diameter of 10 mm at room temperature, with a deformation of 5% per rolling pass, under a vacuum degree < 1×10 -2 Anneal at 800℃ for 2 hours in Pa.

[0030] (5) Then cold drawing, with a deformation of 1% per pass, and finally vacuum at 800℃ with a degree of <1×10 -2 Heat treatment at Pa for 1 hour, and the sample was repeatedly subjected to the above cold drawing and vacuum heat treatment to obtain wire with a diameter of 1 mm.

[0031] (6) The filament is placed in a vacuum of <1×10 -2 Ag-based electrical contact materials were obtained by vacuum heat treatment at 800℃ for 1 hour in Pa.

[0032] Example 3 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Nd: 1%, Y: 1%, with the balance being Ag.

[0033] The preparation method of the Ag-based electrical contact material includes the following steps: (1) Gd blocks, Nd blocks, Y blocks and Ag blocks are prepared according to the element ratio of Ag-based electrical contact material described above.

[0034] (2) Induction melting of the prepared materials: First, pre-vacuum is applied to a degree of <1×10 -2 The pressure is then increased to 1.0 atmospheres and filled with 99.999% argon gas for melting. The process of vacuuming and filling is repeated four times. Then, induction melting is performed to obtain a cylindrical ingot.

[0035] (3) After taking it out and polishing the top and bottom surfaces of the ingot, use an X-ray fluorescence analyzer to measure whether the contents of Y, Nd and Gd on both sides of the ingot are uniform and whether the concentration reaches 1%, 1%, 1%. If they are not uniform and the concentration does not reach the required level, turn the bottom of the ingot up and perform multiple smelting steps (2) until the element contents on the top and bottom sides of the ingot are uniform.

[0036] (4) The material obtained in step (3) is rolled into a wire with a diameter of 10 mm at room temperature, with a deformation of 10% per rolling pass, under a vacuum degree < 1×10 -2 Anneal at 500℃ for 3 hours in Pa.

[0037] (5) Then cold drawing, with a deformation of 4% per pass, and finally vacuum at 500℃ with a degree of <1×10 -2 Heat treatment at Pa for 3 hours, and repeated cold drawing and vacuum heat treatment were performed on the sample to obtain wire with a diameter of 1 mm.

[0038] (6) The filament is placed in a vacuum of <1×10 -2 Ag-based electrical contact materials were obtained by vacuum heat treatment at 800℃ for 0.5 hours in Pa.

[0039] Example 4 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 4%, Nd: 0.01%, Y: 0.01%, with the balance being Ag.

[0040] The preparation method of the Ag-based electrical contact material includes the following steps: (1) Gd blocks, Nd blocks, Y blocks and Ag blocks are prepared according to the element ratio of Ag-based electrical contact material described above.

[0041] (2) Induction melting of the prepared materials: First, induction melting of the prepared materials is carried out in an alumina crucible, with a pre-vacuum degree of <1×10 -2 The pressure is increased to Pa, and then 99.999% argon gas at 1.1 atmospheres is introduced for melting, resulting in a cylindrical ingot.

[0042] (3) After taking it out and polishing the top and bottom surfaces of the ingot, use an X-ray fluorescence analyzer to measure whether the contents of Y, Nd and Gd on both sides of the ingot are uniform and whether the concentrations reach 0.01%, 0.01% and 4%, respectively. If they are not uniform, turn the bottom of the ingot up and smelt it multiple times through step (2) until the element contents on the top and bottom sides of the ingot are uniform.

[0043] (4) The material obtained in step (3) is rolled into a wire with a diameter of 10 mm at room temperature. The deformation per rolling pass is 5%, and the vacuum degree is <1×10 -2 Anneal at 500℃ for 3 hours in Pa.

[0044] (5) Then cold drawing, with a deformation of 4% per pass, and finally vacuum at 500℃ with a degree of <1×10 -2 Heat treatment at Pa for 3 hours, and repeated cold drawing and vacuum heat treatment were performed on the sample to obtain wire with a diameter of 1 mm.

[0045] (6) The filament is placed in a vacuum of <1×10 -2 Ag-based electrical contact materials were obtained by vacuum heat treatment at 850℃ for 0.5 hours in Pa.

[0046] Comparative Example 1 An Ag-based electrical contact material comprises the following elements in weight percentage: Nd: 0.01%, Y: 0.01%, with the balance being Ag.

[0047] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0048] Comparative Example 2 An Ag-based electrical contact material comprises the following elements in weight percentage: Nd: 1.00%, Y: 0.02%, with the balance being Ag.

[0049] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0050] Comparative Example 3 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Y: 0.01%, with the balance being Ag.

[0051] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0052] Comparative Example 4 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Y: 0.02%, with the balance being Ag.

[0053] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0054] Comparative Example 5 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Nd: 0.01%, with the balance being Ag.

[0055] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0056] Comparative Example 6 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Nd: 0.02%, with the balance being Ag.

[0057] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0058] Comparative Example 7 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Ce: 0.01%, Y: 0.01%, with the balance being Ag.

[0059] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0060] Comparative Example 8 An Ag-based electrical contact material comprises the following elements in weight percentage: Ce: 0.01%, Y: 1.0%, with the balance being Ag.

[0061] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0062] Comparative Example 9 An Ag-based electrical contact material comprises the following elements in weight percentage: Lu: 1%, Y: 0.01%, Nd: 0.01%, with the balance being Ag.

[0063] The preparation method of the Ag-based electrical contact material is the same as that in Example 1.

[0064] Comparative Example 10 An Ag-based electrical contact material comprises the following elements in weight percentage: Gd: 1%, Nd: 0.01%, Y: 0.01%, with the balance being Ag.

[0065] The preparation method of the Ag-based electrical contact material includes the following steps: (1) Gd blocks, Nd blocks, Y blocks and Ag blocks are prepared according to the element ratio of Ag-based electrical contact materials described above; (2) Induction melting of the prepared materials: First, induction melting of the prepared materials is carried out in an alumina crucible, with a pre-vacuum degree of <1×10 -2 Pa, and then fill with 99.999% argon gas at a pressure of 1.1 atmospheres for melting, and obtain a cylindrical ingot through melting; (3) After taking it out and polishing the top and bottom surfaces of the ingot, use an X-ray fluorescence analyzer to measure whether the element content on the top and bottom surfaces of the ingot is uniform. If it is not uniform, turn the bottom of the ingot up and perform multiple smeltings through step (2) until the element content on the top and bottom surfaces of the ingot is uniform. (4) The material obtained in step (3) is rolled into a wire with a diameter of 10 mm at room temperature, and the deformation per rolling pass is 11%; (5) At room temperature, the deformation per pass is 3%, and a wire with a diameter of 1 mm is obtained; (6) The wire was vacuum heat-treated at 850°C for 1 hour to obtain Ag-based electrical contact material.

[0066] Example of effect The electrical contact materials prepared in the examples and comparative examples, as well as pure Ag materials, were used. Figure 2 The arc test imaging device shown performs arc measurements under harsh test conditions of DC 25V / 30A. The arc size and arc life are measured by the images captured by the high-speed camera equipment, and the data are shown in Table 1. The arc test imaging device includes an electrical contact testing machine (such as the common JF04C electrical contact testing machine) and a high-speed camera equipment.

[0067] Table 1 As shown in Table 1, compared with pure Ag material, adding two or three elements from Y, Nd, Gd, Ce, and Lu can effectively reduce the arc size and lifespan. However, in Comparative Examples 7-10, the addition of elements such as Ce and Lu, or improper processing and heat treatment, can have the opposite effect, leading to melting due to excessive arc strength, which can easily cause material breakage during processing. According to Example 1 and Comparative Examples 1-6, the absence of a certain element increases the arc diameter and lifespan, indicating that the synergistic effect of Gd, Nd, and Y can effectively reduce the arc diameter and lifespan, and the effect is significantly improved.

[0068] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. An Ag-based electrical contact material, characterized in that, The elements include the following weight percentages: Gd: 1%–4.0%, Nd: 0.01%–1.0%, Y: 0.01%–1.0%, with the balance being Ag; The preparation method of the Ag-based electrical contact material includes the following steps: (1) Gd metal, Nd metal and Y metal are mixed according to the element ratio of the Ag-based electrical contact material; (2) The prepared materials are induction melted to obtain ingots; (3) Measure whether the element content on the top and bottom surfaces of the ingot is uniform. If it is not uniform, turn the bottom of the ingot upward and perform multiple smelting steps (2) until the element content on both the top and bottom surfaces of the ingot is uniform. (4) The material obtained in step (3) is rolled, subjected to a first vacuum annealing heat treatment, repeated drawing and a second vacuum annealing heat treatment to obtain wire; (5) The wire is subjected to a third vacuum annealing heat treatment to obtain Ag-based electrical contact material.

2. The Ag-based electrical contact material as described in claim 1, characterized in that, The induction melting specifically includes: vacuum degree <1×10 -2 Pa, and then argon gas with a pressure of 1.0 to 1.1 atmospheres and a purity of 99.999% is introduced for melting.

3. The Ag-based electrical contact material as described in claim 1, characterized in that, The uniformity of elemental content on the top and bottom surfaces of the spindle was measured using an X-ray fluorescence analyzer.

4. The Ag-based electrical contact material as described in claim 1, characterized in that, The rolling temperature is room temperature, and the deformation per rolling pass is 5-10%.

5. The Ag-based electrical contact material as described in claim 1, characterized in that, The first vacuum annealing heat treatment is performed at a temperature of 400-500℃ for 3 hours, with a vacuum degree <1×10⁻⁶. -2 Pa.

6. The Ag-based electrical contact material as described in claim 1, characterized in that, The drawing temperature is room temperature, and the deformation per pass is 3-4%.

7. The Ag-based electrical contact material as described in claim 1, characterized in that, The second vacuum annealing heat treatment is performed at a temperature of 400-500℃ for 3 hours, with a vacuum degree <1×10⁻⁶. -2 Pa.

8. The Ag-based electrical contact material as described in claim 1, characterized in that, The third vacuum annealing heat treatment is performed at a temperature of 800-850℃ for 0.5 hours, with a vacuum degree <1×10⁻⁶. -2 Pa.